Improving Problem Solving Ability Through Problem Based Learning E-Modules - Nadya Intan Herawati; Insih Wilujeng (Jurnal Penelitian Pendidikan IPA, 2023)
This study aims to produce research instruments that are suitable for use in learning physics using the PBL learning model and to find out the increase in students' problem-solving abilities. The subjects of this study were 70 grade 10 students. This research was a Research and Development (R&D) study using a 4D development model consisting of Define, Design, Development, and Disseminate. The types of research data are qualitative and quantitative. collecting research data using observation and tests of students' problem-solving abilities given before and after learning. The results showed that the research instruments developed were valid for use in physics learning as evidenced by the results of the validity and reliability and the improvement of students' problem-solving skills in the modeling and implementation classes included in the medium category.